The Influence of Entrepreneurial Orientation Dimension on Supply Chain Performance at PT XYZ Jakarta in 2022 - Pratiwi, Sekar Widyastuti; Purwoko, Harry; Akbar, Ghifari Maulana; Firdaus, Muhammad Iqbal; Lermatan, Esterlinus Edwin (Jurnal Logistik Indonesia, 2023)
This thesis aims to analyze the influence of entrepreneurial orientation dimensions on supply chain performance at PT XYZ. The supply chain is a vital element in business, including planning, procurement, production, distribution and delivery of products/services to end consumers. Entrepreneurial orientation includes proactiveness, innovation, and risk taking. This research uses a quantitative approach with survey methods and questionnaires distributed to managers and supply chain staff. Secondary data was obtained from literature, financial reports and company documents. Analysis uses SmartPLS 3.2.9 with variance-based structural equation analysis, measuring and modeling data simultaneously. Samples were taken using a saturated sampling technique. The results show that innovation has no significant positive effect on supply chain performance, while proactiveness and risk taking have a significant positive impact. Exogenous variables (innovation, proactiveness, risk taking) explain 53.1% of supply chain performance, the rest is influenced by other factors. The implications of this research provide guidance for companies to increase supply chain efficiency in competitive and dynamic markets.